The tangle of science : reliability beyond method, rigour, and objectivity - Cartwright, Nancy; Hardie, Jeremy; Montuschi, Eleonora; Soleiman, Matthew; Thresher, Ann C. (Oxford University Press, 2022)
"Science is remarkably reliable. It puts people on the moon, performs laser eye surgery, tells us about ancient civilisations and species, and predicts the future of our climate. What underwrites this reliability? This book argues that the standard answers-the scientific method, rigour, and objectivity-are insufficient for the job. Here we propose a new model of science that places its products front and centre. This is the 'Tangle of Science'. In this book we show how any reliable piece of science is underpinned by a vast, diverse, and thick network of other scientific products. In doing so we bring back into focus areas of science that have been long neglected, emphasising how every product, from the screws that hold the space shuttle together to ways of measuring the consumer price index to Einstein's theory of general relativity, work together to support results we can trust. (146)"--
Keywords: tiede; tieteellinen tieto; luotettavuus; tieteenfilosofia; vetenskap; vetenskaplig kunskap; tillförlitlighet; vetenskapsfilosofi